Students’ Perception of Teachers’ Creativity in Implementing Home Learning at SMK Duta Mas - Nurhayati Nurhayati; Tri Angkarini; Nini Adelina Tanamal (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2021)
The Indonesian government formally enforces rules of study, worship, and work from home from March 16th, 2020. Minimizing and limiting meetings involving physical contact are efforts to reduce the spread of the COVID-19 virus. These conditions have implications for the effectiveness of the learning process in schools. The implementation of a home learning program replacing face to face-to-face schooling raised some problems from the lack of teachers’ skills to hazy educational policies. Because of that reason this study is conducted to find out students’ perception of teachers’ creativity in implementing home learning programs during the pandemic. There were 60 participants chosen by simple random sampling from grade 11th, the academic year 2019-2020, SMK Duta Mas. A questionnaire with a Likert scale was used to collect data. Then data analysis employed qualitative descriptive research to analyse indicators of teachers’ creativity proposed by Slameto. The findings of this study reveal that from 6 indicators of teachers’ creativity, 5 of them have a high percentage and the average total percentage is 79.26%. Therefore, it can be concluded that students’ perception of teachers’ creativity in SMK Duta Mas in implementing home learning during the pandemic is considered high. However, teachers need to improve their ability in creating media for learning because it is very important to improve students’ learning achievement and to motivate them to learn.